Membangun Keamanan Data dalam Kebijakan Satu Data Indonesia: Tinjauan Kritis terhadap Perpres No. 39 Tahun 2019 - Reja Reja; Faris Widiyatmoko; Hesti Rosdiana; Jerry Indrawan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The background for the establishment of Law Number 27 of 2022 concerning Personal Data Protection raises a critical question that the Indonesian government must address, who will oversee and safeguard the security of citizens' data in public administration systems. The purpose of this study is to examine the implementation of One Data Indonesia through Presidential Regulation Number 39 of 2019 (Perpres No. 39 of 2019) regarding One Data Indonesia, which remains a strong foundation for regulating government data governance. Unfortunately, this regulation does not yet include security aspects, which should be one of the principles of One Data Indonesia. This study explores Perpres No. 39 of 2019 as a critique of the regulation. The findings highlight the importance of incorporating security aspects to protect the sovereignty of government data used in public administration, especially in electronic processes conducted domestically. The principle of data security is a crucial component of the implementation of One Data Indonesia, which will be integrated with various other policy products, such as the Presidential Regulation on Electronic-Based Government Systems, the Presidential Regulation on Accelerating Digital Transformation and Integration of National Digital Services, the Law on Information and Electronic Transactions, the Law on Personal Data Protection, and other relevant regulations.